Efektivitas Antidiabetik Oral Baik Tunggalmaupun Kombinasi Pada Pasien Diabetes Mellitus Tipe II Di RSUD Kota Madiun - Kuncara Nata Waskita; Vivi Rosalina (Universitas Muhamadiyah Manado, 2020)
Diabetes Mellitus is a group of chronic metabolic disorders due to abnormal metabolism of carbohydrates, fats, and proteins, characterized by hyperglycemia which is results in long-term microvascular, macrovascular and neuropathic complications. Oral antidiabetic therapy is the main pharmacological therapy to treat type II diabetes mellitus. This therapy can be oral antidiabetic therapy. Thus, to find out the effectiveness of either combination or single of antidiabetics on diabetes mellitus patients, researchers conducted a studies of inpatients at RSUD Madiun. This study included as non-experimental observational study with a cross-sectional study design at RSUD Madiun. Data were collected from Medical Records in October 2018. The sampling method that used in this study was non probability with purposive sampling technique, so there are 58 patients as a total sample. The results showed that the effectiveness of controlling blood sugar levels when using an effective single ADO was Metformin, because Metfomin was able to reduce blood sugar levels with an average length of stay of 6.17 and the effectiveness of controlling blood sugar levels when using an effective combination of ADO was Metformin and acarbosa, because Metfomin and acarbosa are able to reduce blood sugar average length of stay 7 days inpatient.